Colonies of sounds: the role of radio in the sound expression of lusophony - Oliveira, Madalena (2014)
Publicado em "Colonialisms, post-colonialisms and lusophonies: proceedings of the 4th International Congress in Cultural Studies". ISBN 978-989-98219-2-7